Hard candy [videorecording (DVD)] - Nelson, Brian, 1958-; Wilson, Patrick, 1973-; Page, Elliot, 1987-; Oh, Sandra, 1971-; Holmes, Jennifer; Nyman, Molly; Escott, Harry, 1976- (Lions Gate Home Entertainment, 2005)
When a 30-something fashion photographer agrees to a date with a precocious teenager, he gets far more than he bargained for.